Asimetri Informasi dan Greenwashing dalam Era Pemasaran Digital: Peran Strategi Digital Marketing terhadap Persepsi Keberlanjutan Konsumen - Fatchurrohman, Mochamad; Irfana, Maisyatus Su'adaa; Puspitasari, Fanny Dwi; Sari, Fajar Tinovita (LPPM Institut Pendidikan Nusantara Global, 2026)
The rapid expansion of digital marketing has transformed how firms communicate sustainability values, yet it has also intensified information asymmetry between companies and consumers. Such asymmetry creates opportunities for greenwashing, where environmental claims are not fully supported by actual performance. This study examines the effect of information asymmetry on greenwashing and analyzes how digital marketing strategies influence greenwashing and consumer sustainability perceptions. Using an explanatory quantitative design and Structural Equation Modeling–Partial Least Squares (SEM-PLS), the model tests the causal relationships among information asymmetry, digital marketing strategies, greenwashing, and consumer sustainability perceptions. The findings indicate that information asymmetry has a positive and significant effect on greenwashing, while digital marketing strategies exert a significant negative effect on greenwashing and a positive effect on consumer sustainability perceptions. Importantly, the results demonstrate that transparent and evidence-based digital marketing strategies have a stronger role in reducing information asymmetry and mitigating greenwashing practices than promotional approaches that merely amplify sustainability claims. Thus, effective digital marketing when grounded in transparency and interactive engagement contributes more substantially to minimizing information asymmetry and fostering authentic sustainability perceptions among consumers.